Immersion, exposure and learner driven learning through 360-degree videos and VR experiences: Education 4.0 for English teaching / Airil Haimi Mohd Adnan - Mohd Adnan, Airil Haimi (UiTM Press, 2020)
Obstacles, both imagined and real, continue to hinder the wider adoption of Education 4.0 learning technologies although these technologies are now easily available in the mainstream consumer market. At the same time, the boom in Industry 4.0 manufacturing has brought down the prices of these technological tools making them more affordable to all. A case in point is 360-degree spherical video cameras and software that can record, render and playback immersive 'real life' contents. 360-degree spherical video contents can then be rendered and post-processed into VR (virtual reality) experiences that are not just immersive but also allow for limitless exposure time to learners. Both technologies allow for 'learner driven learning' to happen in the truest sense, for instance for English language learners. This research paper examines data collected from 160 undergraduates who were immersed and exposed to 360-degree videos and VR experiences for a degree level course on English for Business and Professional Interactions at a public university campus in northern Malaysia. Even if this unfunded teaching innovation project is only 10 months 'young', the benefits of 360-degree videos and VR experiences in English language content delivery are evident to support learner drive learning: Contents are freely available online and learners can learn anytime, anywhere; total immersion can be achieved using cheap VR goggles powered by learners' smartphones; and, most beneficially, weaker learners who desperately need more time to understand and practice difficult degree level English skills now have the freedom to revise and upskill themselves at their own pace.